Masa Depan Pekerjaan: Mengapa Keahlian Sistem Informasi Manajemen Sangat Diperlukan? - Nuriani Nuriani; Rayyan Firdaus (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
In this digital era, Management Information System (MIS) has become an integral part of human life, including in the world of work. The rapid development of technology changes many aspects of work, requiring individuals to have skills that are in accordance with the demands of the times. One of the skills that are indispensable in the future is Management Information System (MIS) skills. SIM combines information and communication technology (ICT) with business processes and human resources to provide management with accurate and timely information to support decision making, business operations, and internal and external communications. This article discusses about SIM skills are indispensable in the future because SIM can help organizations improve efficiency and effectiveness. SIM graduates have extensive career opportunities in various fields, such as information systems analysts, information systems architects, information systems consultants, information systems managers, and data scientists.